2010
DOI: 10.1007/s11239-010-0445-9
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism risk stratification in medically-ill hospitalized cancer patients. A comprehensive cancer center experience

Abstract: Cancer and its treatment are recognized risk factors for VTE. Compliance rate with published VTE prophylaxis guidelines is low. Decision on when to offer prophylaxis for hospitalized cancer patients is difficult to make. This paper describes current clinical practice in offering VTE prophylaxis to hospitalized cancer patients. Prophylaxis rate and rate of VTE will be correlated with the risk level. We prospectively followed all consecutive adult cancer patients admitted to medical units over a 5-month period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…Of these, 46 reports from 38 individual cohorts (studies) were included in the review [19],[20],[23][66] (Figure 1). There were six separate papers from a single cohort from California (one providing incidence rates of VTE for 15 separate cancer types [33], and five individual reports focussing on cancers of the lung, breast, bowel, brain, and leukaemia [24],[32],[34],[45],[56]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 46 reports from 38 individual cohorts (studies) were included in the review [19],[20],[23][66] (Figure 1). There were six separate papers from a single cohort from California (one providing incidence rates of VTE for 15 separate cancer types [33], and five individual reports focussing on cancers of the lung, breast, bowel, brain, and leukaemia [24],[32],[34],[45],[56]).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were classed as high risk when follow-up commenced following outpatient chemotherapy ( n  = 9), surgery ( n  = 8), inpatient hospitalisation (not specifically for surgery, n  = 2), or a receipt of a mixture of treatment types ( n  = 7), or because either all or the majority of patients had advanced or metastatic cancer at baseline ( n  = 5). Prophylaxis was administered to either some (>20%) or all of the participants in 11 studies; with this intervention taking the form of either anticoagulant prophylaxis (with or without mechanical methods) [23],[31],[47],[53],[55],[58],[59], mechanical prophylaxis only [25],[27], aspirin [42], or unspecified prophylaxis [28]. In a further six studies it was stated explicitly that no patients [20],[26],[37],[38],[43],[44] were receiving anticoagulant prophylaxis, and in two further studies [29],[66] there was a small number (<5%) receiving warfarin or heparin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of this risk model is limited by the small number of patients used to develop this risk model and the need for external validation of the tool. A recent prospective, observational study83 used the Caprini risk assessment model,84 applying it to cancer patients hospitalized because of infections, chemotherapy, or palliative care. This model assigns the same risk score to all patients with cancer, not distinguishing between any features such as the primary site, stage, or active treatment.…”
Section: Risk Stratification and Development Of A Risk Assessment Modelmentioning
confidence: 99%
“…Venous thromboembolism (VTE), including pulmonary embolism (PE) and deep venous thrombosis (DVT), is a major and potentially life-threatening complication among medical inpatients. It has been reported that 50%–75% of cases of VTE in hospitalized patients occur in those being treated for medical conditions, and that the incidence of fatal PE is higher in medical patients compared with surgical patients 1 4 ) . Evidence clearly demonstrates that prophylaxis significantly reduces the incidence of VTE 5 7 ) , and most guidelines recommend the use of prophylaxis for medical inpatients at an increased risk of developing VTE 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%